Analisis Kadar Logam Berat Timbal (PB) pada Makanan Kaleng Daging Giling Berbagai Merk - Panji Ratih Suci; Muh. Latif 'Alim; Sulfika Oriza Nova Sativa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Along with increasingly rapid technological developments in our country, the number of existing industries is increasing. Apart from producing useful products, this industry also produces waste. The waste produced contains a lot of heavy metals, one of which is the heavy metal lead. If the lead metal in the waste receives little treatment, this can cause pollution in the environment, even though this waste is present in small quantities, the lead condition is unstable and if it accumulates in the body, it can ultimately trigger cancer cells (carcinogenic) which can be dangerous for health. . In this research, adsorption of PB2+ ions was carried out on canned ground meat, where heavy metal contamination occurred in the ground meat. This research aims to determine the effectiveness of the absorption of heavy metals (Pb) contained in ground beef and their characteristics. The uptake of PB2+ ions in ground beef, measuring the concentration of PB2+ ions before and after receiving treatment, was carried out using an instrument, namely AAS, at a wavelength of 217nm. The research results showed that the effectiveness of ground beef in absorbing PB2+ ions in canned food was as high as brand a: 0.023; brand b: 0.009; brand c: 0.006